Pharmacological preconditioning by TERT inhibitor BIBR1532 confers neuronal ischemic tolerance through TERT‐mediated transcriptional reprogramming. Issue 4 (9th October 2021) - Xie, Xuemin; Li, Mingxi; Zhou, Mengyao; Chow, Shing Fung; Tsang, Chi Kwan
Abstract: After a sublethal ischemic preconditioning (IPC) stimulus, the brain has a remarkable capability of acquiring tolerance to subsequent ischemic insult by establishing precautionary self‐protective mechanism. Understanding this endogenous mechanism would reveal novel and effective neuroprotective targets for ischemic brain injury. Our previous study has implied that telomerase reverse transcriptase (TERT) is associated with IPC‐induced tolerance. Here, we investigated the mechanism of TERT‐mediated ischemic tolerance. Preconditioning was modeled by oxygen‐glucose deprivation (OGD) and by TERT inhibitor BIBR1532 in primary neurons. We found that ischemic tolerance was conferred by BIBR1532 preconditioning. We used the Cleavage‐Under‐Targets‐And‐Tagmentation approach, a recently developed method with superior signal‐to‐noise ratio, to comprehensively map the genomic binding sites of TERT in primary neurons, and showed that more than 50% of TERT‐binding sites were located at the promoter regions. Mechanistically, we demonstrated that under normal conditions TERT physically bound to many previously unknown genomic loci in neurons, whereas BIBR1532 preconditioning significantly altered TERT–chromatin‐binding profile. Intriguingly, we found that BIBR1532‐preconditioned neurons showed significant up‐regulation of promoter binding of TERT to the mitochondrial anti‐oxidant genes, which were correlated with their elevated expression. Functional analysis further indicated that BIBR1532‐preconditioning significantly reduced ROS levels and enhanced tolerance to severe ischemia‐induced mitochondrial oxidative stress in neurons in a TERT‐dependent manner. Together, these results demonstrate that BIBR1532 confers neuronal ischemic tolerance through TERT‐mediated transcriptional reprogramming for up‐regulation of mitochondrial anti‐oxidation gene expression, suggesting the translational potential of BIBR1532 as a therapeutic agent for the treatment of cerebral ischemic injury and oxidative stress‐induced neurological disorders. Abstract : Despite TERT is well known to bind to telomeric DNA for maintaining their integrity, emerging findings have revealed many non‐telomeric functions of TERT. However, its roles in neurons remain obscured. We discover that TERT regulates genome‐wide transcription in neurons, especially mitochondrial antioxidant genes, for promoting cellular redox homeostasis. We further found that the specific TERT inhibitor BIBR1532, an anti‐cancer agent, exhibits a novel prophylactic neuroprotective effect against subsequent ischemic insult. Results of this study provide a conceptual advance to the fields and may open a new avenue for the translational potential of BIBR1532 in preventing ischemic injury resulted from neurological disorders.